Health system frameworks and performance indicators in eight countries: A comparative international analysis. (4th January 2017) - Braithwaite, Jeffrey; Hibbert, Peter; Blakely, Brette; Plumb, Jennifer; Hannaford, Natalie; Long, Janet Cameron; Marks, Danielle
Objectives: Performance indicators are a popular mechanism for measuring the quality of healthcare to facilitate both quality improvement and systems management. Few studies make comparative assessments of different countries' performance indicator frameworks. This study identifies and compares frameworks and performance indicators used in selected Organisation for Economic Co-operation and Development health systems to measure and report on the performance of healthcare organisations and local health systems. Countries involved are Australia, Canada, Denmark, England, the Netherlands, New Zealand, Scotland and the United States. Methods: Identification of comparable international indicators and analyses of their characteristics and of their broader national frameworks and contexts were undertaken. Two dimensions of indicators – that they are nationally consistent (used across the country rather than just regionally) and locally relevant (measured and reported publicly at a local level, for example, a health service) – were deemed important. Results: The most commonly used domains in performance frameworks were safety, effectiveness and access. The search found 401 indicators that fulfilled the 'nationally consistent and locally relevant' criteria. Of these, 45 indicators are reported in more than one country. Cardiovascular, surgery and mental health were the most frequently reported disease groups. Conclusion: These comparative data inform researchers and policymakers internationally when designing health performance frameworks and indicator sets.